'Posture second' strategy predicts disability progression in multiple sclerosis. (June 2021) - Castelli, Letizia; Quartuccio, Maria Esmeralda; Ruggieri, Serena; De Giglio, Laura; Prosperini, Luca
We assessed 168 patients with multiple sclerosis (MS) by force platform to obtain the dual-task cost (DTC) of balance, that is, the change in postural sway from quiet standing to dual-task condition (Stroop test). After a median follow-up time of 3.5 years from this assessment, disability progression occurred in 45 (27%) patients. Disability progression was predicted by the adoption of a 'posture second' strategy, that is, values of DTC of balance exceeding those obtained from 62 healthy controls, even after controlling by demographic and clinical characteristics. The DTC of balance may potentially represent a novel and easy tool to predict MS progression.